Outbreak investigations and molecular characterization of foot‐and‐mouth disease viruses circulating in south‐west Niger. Issue 1 (27th March 2017) - Souley Kouato, B.; Elliot, F. M.; King, D. P.; Hyera, J.; Knowles, N. J.; Ludi, A. B.; Mioulet, V.; Matlho, G.; De Clercq, K.; Thys, E.; Marichatou, H.; Issa, S.; et al.
Summary: In Niger, the epidemiological situation regarding foot‐and‐mouth disease is unclear as many outbreaks are unreported. This study aimed (i) to identify Foot‐and‐mouth disease virus (FMDV) strains currently circulating in cattle herds, and (ii) to identify risk factors associated with Foot‐and‐mouth disease (FMD)‐seropositive animals in clinical outbreaks. Epithelial tissues ( n = 25) and sera ( n = 227) were collected from cattle in eight districts of the south‐western part of Niger. Testing of clinical material revealed the presence of FMDV serotype O that was characterized within the O/WEST AFRICA topotype. The antigenic relationship between one of the FMDV isolates from Niger (O/NGR/4/2015) and three reference vaccine strains was determined by the two‐dimensional virus neutralization test (2dmVNT), revealing a close antigenic match between the field isolate from Niger and three FMDV serotype O vaccine strains. Serological analyses using a non‐structural protein (NSP) test provided evidence for previous FMDV infection in 70% (158/227) of the sera tested. Multivariate logistic regression analysis revealed that only the herd composition (presence of both cattle and small ruminants) was significantly associated with FMDV seropositivity as defined by NSP‐positive results ( p ‐value = .006). Of these positive sera, subsequent testing by liquid‐phase blocking ELISA (LPBE) showed that 86% (136/158) were positive for one (or more) of four FMDV serotypes (A, O, Southern African Territories (SAT) 1 and SAT 2). This study provides epidemiological information about FMD in the south‐western part of Niger and highlights the complex transboundary nature of FMD in Africa. These findings may help to develop effective control and preventive strategies for FMD in Niger as well, as other countries in West Africa.